Institutional Review: Open Access and Open Knowledge Production Processes: Lessons from CODESRIA - Nyamnjoh, Francis (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2010)
It is common in discussions of open access to limit the issue to publications and dissemination. This conflates accessibility with recognition and representation, and supposes that competing and conflicting knowledge systems and ideas would be equally available and affordable if room were created for multiple channels of accessibility. Such enthusiasm and euphoria, while understandable, do not adequately account for the prevalent power relations that structure knowledge production into interconnecting hierarchies at local and global levels. CODESRIA has some lessons to draw on from its experience of the past 37 years – lessons about the need to privilege and prioritise recognition and representation of the perspectives, epistemologies, and contextual and methodological diversity that inform knowledge production globally and locally; and lessons about the need to widen our understanding and discussion of ‘open access’ to go beyond just enabling access to knowledge and research results through a multiplicity of dissemination possibilities. It is important to discuss opening access up to different races, places, spaces, cultures, classes, generations, disciplines and fields of study. This review presents CODESRIA, and its ever-evolving publications and dissemination policy, as a possible model to inform and inspire institutions interested in a comprehensive idea of open access in an interconnected world of local and global hierarchies, where producing and consuming difference is part and parcel of everyday life.